New scenarios for safe mobility in urban areas: emerging topics from an international debate - Pezzagno, Michèle; Richiedei, Anna (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The paper presents the emerging topics of the international debate for safe mobility in urban areas with an innovative interpretation. This is the bibliometric mapping of the most recurrent concepts (keywords) of almost 80 scientific publications. The paper framework moves from the issue of the “sustainability” of cities to the “safe” and “innovative” city through a mobility lens. In Europe by 2030 cities have to become climate-neutral and some main urban strategy to achieve this result is focused on transport and mobility sectors. The interpretation of the bibliometric mapping results leads to highlighting the shortcomings of some topics within the scientific debate. The Qualiquantitaive Data Analysis was applied to set the interdependency among research fields and better understand the interrelation among the different topics. The key concepts of ‘time’ and ‘innovation’ don’t emerge clearly as an object of research and they will be included in future reflections about the transformative capacity of the city through sustainability and in the development of city strategies.